Topology-Based Three-Dimensional Reconstruction of Delicate Skeletal Fossil Remains and the Quantification of Their Taphonomic Deformation - Demuth, Oliver E.; Benito, Juan; Tschopp, Emanuel; Lautenschlager, Stephan; Mallison, Heinrich; Heeb, Niklaus; Field, Daniel J. (Frontiers in Ecology and Evolution, 2022)
Taphonomic and diagenetic processes inevitably distort the original skeletal morphology of fossil vertebrate remains. Key aspects of palaeobiological datasets may be directly impacted by such morphological deformation, such as taxonomic diagnoses and phylogenetic hypotheses, interpretations of the shape and orientation of anatomical structures, and assessments of interspecific and intraspecific variation. In order to overcome these ubiquitous challenges we present a novel reconstruction workflow combining retopology and retrodeformation, allowing the original morphology of both symmetrically and asymmetrically damaged areas of fossils to be reconstructed. As case studies, we present idealised three-dimensional reconstructions of the sternum of the crownward stem-bird Ichthyornis dispar, and cervical vertebrae of the diplodocid sauropod Galeamopus pabsti. Multiple Ichthyornis sterna were combined into a single, idealised composite representation through superimposition and alignment of retopologised models, and this composite was subsequently retrodeformed. The Galeamopus vertebrae were individually retrodeformed and symmetrised. Our workflow enabled us to quantify deformation of individual specimens with respect to our reconstructions, and to characterise global and local taphonomic deformation. Our workflow can be integrated with geometric morphometric approaches to enable quantitative morphological comparisons among multiple specimens, as well as quantitative interpolation of ‘mediotypes’ of serially homologous elements such as missing vertebrae, haemal arches, or ribs.